2016
DOI: 10.1007/s00330-016-4537-6
|View full text |Cite
|
Sign up to set email alerts
|

Low contrast medium-volume third-generation dual-source computed tomography angiography for transcatheter aortic valve replacement planning

Abstract: • Third-generation dual-source CT facilitates low-tube-voltage acquisition. • TAVR planning can be performed with reduced contrast volume and radiation dose. • TAVR-planning CT did not result in changes in creatinine levels at follow-up. • TAVR candidates can be safely evaluated by comprehensive low-tube-voltage CT angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…In discordant scores, a consensus reading was performed between the two observers. The IQ of the attenuation of the coronary was assessed with a 5-point Likert scale as follows: score of 1, insufficient attenuation resulting in a non-diagnostic examination; 2, poor, suboptimal attenuation with low diagnostic confidence; 3, fair, acceptable attenuation of relevant cardiac anatomy and vascular access; 4, good, satisfactory attenuation providing sufficient evaluation of relevant anatomy; 5, excellent, strong attenuation of even the smallest arteries [9]. The presence and extent of image artifact was assessed with the 5-point Likert scale as follows: score of 1, non-diagnostic, severe artifact; 2, poor, substantial artifact but sufficient contrast attenuation for assessing the heart system; 3, fair, moderate artifact not interfering with a comprehensive examination of the coronary artery; 4, good, with only minor artifact not interfering with assessment; 5, excellent, with no artifact or any diagnostic limitation [9].…”
Section: Qualitative Image Assessmentmentioning
confidence: 99%
“…In discordant scores, a consensus reading was performed between the two observers. The IQ of the attenuation of the coronary was assessed with a 5-point Likert scale as follows: score of 1, insufficient attenuation resulting in a non-diagnostic examination; 2, poor, suboptimal attenuation with low diagnostic confidence; 3, fair, acceptable attenuation of relevant cardiac anatomy and vascular access; 4, good, satisfactory attenuation providing sufficient evaluation of relevant anatomy; 5, excellent, strong attenuation of even the smallest arteries [9]. The presence and extent of image artifact was assessed with the 5-point Likert scale as follows: score of 1, non-diagnostic, severe artifact; 2, poor, substantial artifact but sufficient contrast attenuation for assessing the heart system; 3, fair, moderate artifact not interfering with a comprehensive examination of the coronary artery; 4, good, with only minor artifact not interfering with assessment; 5, excellent, with no artifact or any diagnostic limitation [9].…”
Section: Qualitative Image Assessmentmentioning
confidence: 99%
“…Bitter, et al 20) used 38 mL CM using a third-generation DSCT system, allowing comprehensive imaging for procedural success. Felmy, et al 21) investigated the scope for reducing the CM dose in CTA for TAVI screening, and compared CTA using a thirdgeneration DSCT system (70 kV, 40 mL CM) with CTA using a second-generation DSCT system (100 kV, 60 mL CM). However, there was no report comparing low tube voltage and conventional tube voltage using thirdgeneration DSCT in patients for TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study by Kim et al, CM volume usage in coronary CTA performed with 320-row CT could be decreased from 60 to 40 ml with preserved image quality and diagnostic accuracy [ 16 ]. In addition, Felmly et al demonstrated that with the latest generation dual source CT a comprehensive transcatheter aortic valve replacement planning was feasible with reduced CM volumes [ 17 ]. In line with these findings, Mangold et al demonstrated that the use of automated tube voltage selection and CM volume adjustment reduces CM volumes and provides excellent image quality and optimal intravascular attenuation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%